A critical review of techniques to determine the magnet temperature of permanent magnet synchronous motors under real-time conditions. Issue 1 (2nd January 2016) - Wallscheid, Oliver; Huber, Tobias; Peters, Wilhelm; Böcker, Joachim
Abstract : The permanent magnet synchronous motor (PMSM) is widely applied in highly utilised automotive traction drives and other industrial applications. With regards to the device life-time, thermal utilisation, safe operation and control performance, the permanent magnet temperature is of great interest. Since a direct magnet temperature measurement is not feasible due to constructional and cost issues in most applications, this contribution gives a review on state-of-the-art model-based magnet temperature determination techniques regarding PMSM. In this context, the existing publications can be classified into thermal models, flux observers and voltage signal injection approaches. Firstly, brief introductions of these methods are given, followed by a direct comparison regarding drawbacks and benefits. This evaluation exhibits the individual constraints of each approach motivating their fusion as an outlook of further investigations in this research field.